Lizzie Bright and the Buckminster boy - Schmidt, Gary D. (New York : Clarion Books, 2004)
In 1911, Turner Buckminster hates his new home of Phippsburg, Maine, but things improve when he meets Lizzie Bright Griffin, a girl from a poor, nearby island community founded by former slaves that the town fathers--and Turner's--want to change into a tourist spot.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Junior High School.
5.9
5-8
Keywords: Clergy -- Juvenile fiction; Historical fiction; Moving, Household -- Juvenile fiction; Progress -- Juvenile fiction; Race relations -- Juvenile fiction; Clergy -- Fiction; Historical fiction; Moving, Household -- Fiction; Progress -- Fiction; Race relations -- Fiction; Clergy -- Fiction; Historical fiction; Moving -- Fiction; Progress -- Fiction; Race relations -- Fiction; Maine -- History -- 20th century -- Juvenile fiction; Maine -- History -- 20th century -- Fiction; Maine -- History -- Fiction